Foreword: About the Institute for Global Legal Studies - Stephen H. Legomsky (Washington University Journal of Law & Policy, 2001)
The Institute for Global Legal Studies will be a vessel for gathering, sustaining, and expanding a broad range of international projects of benefit to our students, our faculty, and the larger society. Through a combination of education and research initiatives, the Institute will draw on international, foreign, and comparative law to expand our knowledge and understanding of contemporary problems and contribute to their solutions. It will prepare students to practice law, and to develop policy, in the globalized society in which they will live and work. It will utilize the vast pool of talent overseas and promote interaction between the students and faculty of Washington University and their colleagues from other nations. In the process, the Institute will foster the lively international environment within the four walls of the law school and throughout the Washington University campus.
Keywords: Globalization; Washington University